Estudio de la velocidad de degradación de azúcares reductores en el proceso de pasteurización de puré de banano aséptico no acidificado sin semilla. - Loayza Aguilar, María D. (2015)
This research aimed to determine the degradation of reducing sugars present in the mashed bananas seedless non-acidified, prepared by the food industry CONFOCO S.A. by applying three different pasteurization conditions (60 ° C for 1 hour, 70 ° C for 1 hour, 80 ° C for 1 hour) using mathematical models and calculating the reaction order of the degradation kinetics of the mash